Handover training: does one size fit all? The merits of mass customisation. Issue 1 (30th October 2012) - Kicken, Wendy; Van der Klink, Marcel; Barach, Paul; Boshuizen, HPA
Abstract : Background: Experts have recommended training and standardisation as promising approaches to improve handovers and minimise the negative consequences of discontinuity of care. Yet the content and delivery of handover training have been only superficially examined and described in literature. Objective: The aim of this study was to formulate recommendations for effective handover training and to examine whether standardisation is a viable approach to training large numbers of healthcare professionals. Methods: A training needs analysis was conducted by means of a questionnaire, which was filled out by 96 healthcare professionals in primary and secondary care in the Netherlands, Spain, Sweden and Poland. Preferences and recommendations regarding training delivery aspects and training topics that should be included in the handover training were measured. Results: The majority of the participants recommended a short conventional training session with practice assignments, to be completed in small, multidisciplinary groups. Formal examination, e-learning and self-study were not favoured. Recommended training topics were: communication skills, standardised procedures, knowing what to hand over, alertness to vulnerable patient groups and awareness of responsibility. Conclusions: The idea of completely standardised handover training is not in line with the identified differences in preferences and recommendations between different handover stakeholders. Mass customisation of training, in which generic training is adapted to local or individual needs, presents a promising solution to address general and specific needs, while containing the financial and time costs of designing and delivering handover training.